2016
DOI: 10.1093/conphys/cow056
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ecological physiology of native and invasive frog species: do invaders perform better?

Abstract: Biological invasions are an important threat to biodiversity. We studied the effect of thermal acclimation on thermal tolerance and locomotor performance in the invasive Xenopus laevis and the Chilean native Calyptocephalella gayi. We show that X. laevis is a better performer than C. gayi. Furthermore, thermal tolerance did not differ between the species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…For example, invasive cane toads have been shown to rapidly evolve dispersal phenotypes due to spatial sorting (Shine et al 2011). Whereas certain life history and phenotypic traits of invading species may facilitate expansion by enabling them to outcompete indigenous species (Catford et al 2008;Cortes et al 2016), others may prove to be disadvantageous to the invader when environmental conditions change (Simberloff and Gibbons 2004). This suggests that a high degree of plasticity or adaptability would be beneficial for invasive species.…”
Section: Introductionmentioning
confidence: 99%
“…For example, invasive cane toads have been shown to rapidly evolve dispersal phenotypes due to spatial sorting (Shine et al 2011). Whereas certain life history and phenotypic traits of invading species may facilitate expansion by enabling them to outcompete indigenous species (Catford et al 2008;Cortes et al 2016), others may prove to be disadvantageous to the invader when environmental conditions change (Simberloff and Gibbons 2004). This suggests that a high degree of plasticity or adaptability would be beneficial for invasive species.…”
Section: Introductionmentioning
confidence: 99%
“…Our study adds to a large body of literature involving physiological comparisons of non‐native species to native ones (e.g., Cortes et al, 2016; Lehmann et al, 2015; Lockwood & Somero, 2011; Marras et al, 2015). Moreover, these results dovetail with a large‐scale meta‐analysis of the role of thermal tolerance on the invasion potential of ectotherms (Kelley, 2014).…”
Section: Discussionmentioning
confidence: 79%
“…The inability of our study to detect significant differences in thermal tolerance breadth between native and invasive species may be related to the number of analysed species, since previous findings for plants (Rejmánek and Richardson 1996), epibenthic marine species (Zerebecki and Sorte 2011) and tropical and sub-Antarctic springtails (Janion-Scheepers et al 2018 have supported the Eurythermality hypothesis. However, published studies for other ectotherms such as amphibians and insects, have also found opposite results (Barahona-Segovia et al 2016, Cortes et al 2016). In the latter case, authors have made a call for caution when interpreting their results, as the trait they measured (locomotion) is produced by complex biochemical and metabolic mechanisms (the discussion by Cortes et al 2016).…”
Section: Hypogastrura Assimilismentioning
confidence: 94%
“…However, published studies for other ectotherms such as amphibians and insects, have also found opposite results (Barahona-Segovia et al 2016, Cortes et al 2016). In the latter case, authors have made a call for caution when interpreting their results, as the trait they measured (locomotion) is produced by complex biochemical and metabolic mechanisms (the discussion by Cortes et al 2016). Even so, thermal tolerance breadth (CT range ) is not the only characteristic that confers an advantage for invasive species to establish in new regions (Kleunen et al 2010, Kelley 2014.…”
Section: Hypogastrura Assimilismentioning
confidence: 94%